ORIENTATION TOWARDS CORPORATE SOCIAL RESPONSIBILITIES: A STUDY OF NON-BUSINESS STUDENTS IN HONG KONG - Wong, Po May Daphne (PEOPLE: International Journal of Social Sciences, 2018)
In many ways our daily livings are shaped by business decisions.As studentsare future decision-makers of their profession, there is a needto educate them with a strongersense of ethicality and corporate social responsibility(CSR)(Evans and Weiss, 2008; Mohammad, 2011).Beforewe can identifyeffective ways in changingstudents’ orientation towards CSR(CSRO), we first need to devise a way inassessinga person’s CSRO.Using Carroll’s (1979)CSR constructsof Economic, Legal, Ethical and Discretionary(Philanthropy), Aupperle (1982) validateda forced-choice scale (E-CSRO) to assess a person’sCSRO. Wong (2017) translateditinto Chinese (C-CSRO)and tested with N=793 Chinese business studentsin Hong Kong.This studyfurther validated C-CSRO with N=827 non-businessChinese studentsandexaminedtheirCSRO.Sampleswere randomly halvedinto two N=383and N=444.Sample 1 showedC-CSRO hashigh item reliability (.915 to -.783);Exploratory Factor Analysisrevealeditsfactor structureissimilar toE-CSRO.Confirmatory Factor Analysis on Sample 2 supportedadequate model fit.Overall mean score ranking of the four CSRO in descending order of importance were Legal, Economic, Ethical and Discretionary.Gender and programme streamsin particular havesignificant effects (p < .05)overthe Economic and Discretionarydimensions.Avenues for future research cantest C-CSRO in other Chinese communities using cross group CFA on measurement invariance; explore influence from other moderating variables onCSRO so that impactful educational initiatives to specific studen tgroup can be found.